INNOVATIVE APPROACH TO DEVELOPMENT INITIATIVE IN STUDENTS - Chankayev O'ljaboy Achilovich; Xushvakov Nurxon Yusupovich; Asatillayev Jahongir Ne'matjon o'g'li; Haydarov Shohruh To'lqin o'g'li (Web of Journals Publishing, 2024)
Motives and attitudes towards the profession as a whole influence the effectiveness of students' studies, which significantly affects the overall level of professional training. The motives for educational activities include: focus on obtaining knowledge, a profession, a diploma. Computer technology plays an important role in maintaining this criterion. New information technologies in the educational process are a powerful activating tool. Their use in natural science education makes it possible to intensify the educational process and make it more effective, because the nature of interaction between subjects of the educational process changes towards their greater individualization and practical orientation. A high level of competence of a university teacher in the field of educational technologies is one of the key conditions for the effectiveness of the process of their design and implementation in the conditions of an innovative educational process at a university.
Keywords: Motivation, students, education, acmeological approach